2021
DOI: 10.1177/0306624x211022667
|View full text |Cite
|
Sign up to set email alerts
|

The Good, the Bad, and the Ugly? A Triarchic Perspective on Psychopathy at Work

Abstract: Does psychopathy have an upside in vocational contexts? Applying the triarchic model of psychopathy, we propose that the dimensions of boldness, disinhibition, and meanness have different relations to workplace outcomes. Focusing on boldness and in line with socioanalytic personality theory, we propose that political skill moderates the relation between boldness and job performance. Using a sample of 477 target-coworker pairings, we found interaction effects of boldness and political skill on contextual and ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 82 publications
1
15
0
Order By: Relevance
“…More specifically, Hogan and Shelton (1998) suggested that social skill moderates the relationship between personality and job performance (and other work outcomes). Following this theoretical lineage, a number of studies have investigated the interactive effects of personality and political skill (Blickle et al, 2020;Blickle et al, 2010;Sun and van Emmerik, 2015;Dietl et al, 2017;Kranefeld and Blickle, 2021;Sch€ utte et al, 2018). Indeed, the literature presents a dynamic relation between dispositional or personal ability factors and political skill.…”
Section: Notable Future Research Considerationsmentioning
confidence: 99%
“…More specifically, Hogan and Shelton (1998) suggested that social skill moderates the relationship between personality and job performance (and other work outcomes). Following this theoretical lineage, a number of studies have investigated the interactive effects of personality and political skill (Blickle et al, 2020;Blickle et al, 2010;Sun and van Emmerik, 2015;Dietl et al, 2017;Kranefeld and Blickle, 2021;Sch€ utte et al, 2018). Indeed, the literature presents a dynamic relation between dispositional or personal ability factors and political skill.…”
Section: Notable Future Research Considerationsmentioning
confidence: 99%
“…Next, the large majority of this study examined psychopathy facets of the triarchic model in relation to a broad range of objective and subjective work outcomes (Blickle et al, 2018; Du & Templer, 2022; Kranefeld & Blickle, 2022; Neo et al, 2018; Schütte et al, 2018; Sutton et al, 2020; Vergauwe et al, 2021). Although each of these studies yield a unique set of findings, one common thread is that boldness is often found to be associated with more positive work‐related outcomes, whereas disinhibition and especially meanness generally demonstrate negative effects on people's performance or, in the case of managers, subordinate performance.…”
Section: A Review Of Nonlinear Interactive Differential and Reciproca...mentioning
confidence: 99%
“…For instance, Fanti et al (2021) reported that the level of parental impulsive-irresponsibility traits specifically predicted increased risk of psychopathology in adolescent children. Notably, in one study ( Kranefeld et al, 2022 ), the different components of psychopathy—at least as conceptualized in the triarchic model—bore opposite relations with outcomes in the workplace. Specifically, while meanness and disinhibition had positive relations with counterproductive work behavior, boldness traits had positive associations with career success (although this was contingent on high levels of political skills as well).…”
Section: The Implications Of Examining Overall Levels Of Psychopathy ...mentioning
confidence: 99%
“…Further, Polaschek et al (2021) reported that the link between recidivism and the triarchic component of disinhibition was partially explained by poorer subjective well-being. Crucially, these mediating or moderating roles appear to differ across context, age, and individual components of the broader psychopathy constructs (e.g., Kranefeld et al, 2022 ). Research on mediators and moderators of the impact of psychopathy is vital to inform theoretical models of its developmental pathways, and to facilitate the development of targeted preventive and treatment efforts.…”
Section: The Quest For Relevant Mediators and Moderatorsmentioning
confidence: 99%
See 1 more Smart Citation